(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
A comprehensive theory of the physical picture of a p-n junction under all injection conditions has been presented in this paper. The pn product in a junction must always be ≤ n1²eqVkT. By incorporating all suitable modification of the boundary conditions, the inconsistencies concerning the relation of the applied potential difference to the difference across the space charge region of a p-n junction were observed. Attempt were made to remove those inconsistencies. The transition region for abrupt p-n junction is analyzed in terms of carrier densities at the neutral bulk-space charge region boundaries and location of these boundaries with respect to the metallurgical junction and also analyzed by using quasi-equilibrium assumptions. The p-n junction is solved by using three-region approach and analytical solutions are derived for low, medium and high injections. Key words: Depletion region, Injection conditions, Quasi-Fermi-level Inconsistencies. DOI: 10.3329/bjsir.v44i3.4398 Bangladesh J. Sci. Ind. Res. 44(3), 265-270, 2009